FACTORS RELATED TO THE PARTICIPATION OF MOTHERS OF TODDLERS IN POSYANDU ACTIVITIES - Irma Suri Amsriani; Agustina Agustina; Vera Nazhira Arifin (Getsempena Health Science Journal, 2026)
Integrated Service Posts (Posyandu) is a public health service program organized by the Indonesian government with the aim of improving the health and welfare of the community, especially mothers and children. Based on theory and previous research, several factors related to the utilization of Posyandu services can be identified, including education, knowledge, attitudes, employment, family support, and the role of cadres. The study employed a quantitative method and a cross-sectional approach. The study population was mothers of toddlers, with a sample size of 105 people selected using a total sampling technique. The results of the univariate analysis showed that 52.4% of mothers utilized Posyandu services, 27.6% utilized them poorly, and 20.0% did not utilize them. Mothers with a primary education level were 29.5%, a secondary education level 40.0%, and a high education level 30.5%. Mothers with low education level 11.4%, medium education level 19.0%, and high education level 69.5%. Mothers with positive attitudes: 64.8%;negative attitudes: 35.2%. Mothers who were employed 67.6% and unemployed 32.4%. Mothers with good family support 47.6% and less than adequate support 52.4%. Meanwhile, cadres who played a role were 80.0%, and those who did not play a role were 20.0%. Bivariate analysis results revealed a relationship between knowledge, attitudes, occupation, family support, the role of cadres, and the participation of mothers of toddlers in Posyandu activities Occupation and the role of cadres were the most dominant factors associated with the participation of mothers of toddlers in Posyandu activities. Therefore, it is hoped that Posyandu cadres can be further empowered, trained, and optimally supported to enable them to deliver professional, communicative, and inspiring messages.